The concept of mind as reflective totality. - Forde, Francis Patrick. (University of Ottawa (Canada), 1978)
This study concerns a significant but hitherto undeveloped concept in the thinking of Saint Thomas Aquinas regarding man; a concept which is rich in implication for modern psychology, dynamic and developmental particularly. St Thomas Aquinas is well known for his solution to the problem of mind-body duality in man; what has been little appreciated is that solving this problem as he did, in terms of Aristotelian hylomorphism, was for St Thomas an intermediary step towards solving a more pressing cognitional problem affecting the basic integrity of the human mind: the problem of the duality of sense and reason. His answer to this further problem is found in his concept of the mind as a totum potentiale, or reflective totality. In this concept, not only the integrity of the human mind but the reality of man himself is presented, not as a given of nature, but as a challenging possibility only. The explanation, development and evaluation of the human mind as a totum potentiale is the subject of this present thesis. A totum potentiale, considered generally, is a totality or complexity of power, a dynamic totality, made up of part-powers. Its peculiar significance is that each part-power shares in the capacity of the whole but, while one power possesses that capacity in its fulness, the others share in it only in a decreasing series of less perfect ways. St Thomas' application of this concept to man's mind leads to certain conclusions whose significance for human life and living this thesis explores. First, the human mind is a complex totality; a complexus of powers, all deriving from a single dynamic source, intellect or understanding, the distinctive characteristic of man. These manifold powers are ramifications of intellect and, without them, intellect, which begins as a possibility only, could not achieve actualization. Secondly, the human mind is a reflective totality; it constitutes itself as an actual understanding through a return to itself, having posited itself in sensibility in its effort to understand reality. Thirdly, self-awareness likewise is not a given but a goal; it derives progressively through consciousness of the other; the human mind comes to know itself only through positing itself in sense. Fourthly, there is no exteriority of sense and intellect. Intellect exists within sensibility; it always permeates and is permeated by sensibility. While it is clear, as this study claims, that the potential or reflective totality concept was central to St Thomas' view of man's mind, its capacities, functioning and growth, St Thomas nowhere presents a developed body of theory on the subject. The present study attempts, by presenting and examining the major texts and their contexts, to uncover the image of the human mind as St Thomas envisioned it and to describe it, not structurally nor statically, but from the viewpoint of a dynamic and humanist psychology and in line with the approach of modern Hermeneutics, one of whose basic principles is that earlier concepts need to be periodically re-examined in the light of later developments within the same or related disciplines and so be made applicable and relevant to the needs of later times. It is the contention of the writer that the implications of the psyche for today's psychology lie in St Thomas' concept of mind as a totum potentiale. In support of this contention, four major areas of application of the concept are selected and considered: its application to the notion of subject; to the role and responsibility of society; to psychotherapy; to human sensitivity. To the extent that modern psychology is seen and recognized to be in need of a concept of mind which is both profound and adequate to encompass all of the human reality, the writer suggests that such a concept is available in St Thomas' presentation of mind as potential totality; potential spirit and subject, source and seat of autonomy, spontaneity and inviolability.
Keywords: Philosophy.